ANALISIS PENGARUH VARIABEL MONETER TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Puspitasari, Emayli Rosdwiati; Septiani, Yustirania (Transpublika Publisher, 2022)
The purpose of the analysis in this study is to determine the effect of the relationship between inflation, foreign exchange rates, and the money supply (M1) on economic growth in Indonesia. The model used is ARDL-ECM (Autoregressive Distributed Lag-Error Correction Modelm with time series data as many as 30 objects studied, starting from 1991 to 2020. In the use of data from the World Bank, one data from the Indonesian Ministry of Trade, and other sources. This study concludes that the inflation variable in the long term has a positive effect and is related to economic growth. The exchange rate variable gives the result that in the long term and short term it has a negative effect and is not related to economic growth. Finally, the M1 variable in the long-term model produces a positive influence and is related to economic growth, then in the short term it has a negative influence and is not related to economic growth in Indonesia.